A (in)acessibilidade artístico-cultural para surdos na cidade de Campo Grande/MS - Katicilayne Roberta de Alcantara (2021)
This final paper is the result of research linked to the Graduate Program in Cultural Studies, at the Aquidauana Campus, from the Federal University of Mato Grosso do Sul Foundation, and discusses, as a central question, whether city of Campo Grande, State of Mato Grosso do Sul bets on artistic accessibility -cultural to the deaf as a way to conquer and reinforce their identity and attractiveness. and if the forms of artistic-cultural accessibility serve the deaf in city of Campo Grande, State of Mato Grosso do Sul? Thus, the general objective is to analyze the narratives of the deaf about the current situation of artistic-cultural accessibility in Campo Grande city. As a theoretical framework, the discussions are based in the field of Postcolonial Studies and Deaf Studies, whose main authors are Homi K. Bhabha, Jorge Larrosa, Carlos B. Skliar, Gladis T.T. Perlin, Maura C. Lopes and Alfredo Veiga-Neto. The data production was inspired by ethnographic procedures, in addition to the use of semi-structured interviews (recorded in Libras and transcribed into Portuguese) with eight deaf signatory participants residing in the Campo Grande city. Based on the analyzed data and from the theoretical discussion, the results show how the deaf are dissatisfied and how the legislation is fragile in its execution, since the political bodies that should provide accessibility conditions for the deaf have the intention of "include” or “give access”, regardless of the creation and promotion of deaf productions in Libras. It was also observed that, resisting this, deaf productions circulate in society, however, in the Campo Grande city, many of them are restricted to the deaf community, without revealing the deaf culture and its various nuances, little known and explored. In this sense, it was noticed that the importance of Libras as responsible for the contact and approximation of the deaf and their peers, as well as the TILS, which demonstrate the need for adequate linguistic-cultural training and constant professional improvement, as it occupies a place dialogical, enabling creations from the elements that compose the artistic-cultural productions. Keywords: Accessibility; Deaf; Artistic-cultural; Libras; Translator and Interpreter of Libras-LP.